Influence of Indian cedar particle pretreatments on cement-wood composite properties - Oliveira, Carolina A. B. [UNESP]; Silva, João V. F. [UNESP]; Bianchi, Natália A. [UNESP]; Campos, Cristiane I. [UNESP]; Oliveira, Karina A. [UNESP]; Galdino, Danilo S. [UNESP]; Bertolini, Marilia S. [UNESP]; Morais, Cesar A. G. [UNESP]; de Souza, Alexandre J.D. [UNESP]; Molina, Julio C. [UNESP] (BioResources, 2020)
This work physically, mechanically, and chemically characterized the composites produced from Portland CP II-E32 cement and fresh Indian cedar wood particles previously treated by immersion in hot and cold water. Density values for wood particulate composites were around 50% lower compared with the wood-free control treatment, from 0.88 to 1.78 g/cm. A larger swelling was observed for the composite material. The results of compressive strength and stiffness indicated that there is no need for particle treatment for composite production. Hot and cold water immersion treatments reduced the total Indian cedar wood extractives by 33% and 42%, respectively. Optical microscopy analysis was used to identify adhesion failures between the cement/wood interface of the composite produced with fresh particles, which presented a higher percentage of extractives. This result indicated that the greater concentration of total extractives partially inhibits the matrix-matrix interaction reinforcement. Despite the reduction in total extractives caused by the treatments, this process is not necessary for the composite production because there is no statistical difference between the treatments. The values obtained for the composite indicate the possibility of application in sealing blocks in light construction systems.
Keywords: Cedar wood; Cementitious composite; Lignocellulosic materials; Wood panels